Pengembangan Potensi Unit Usaha Pondok Pesantren Nurul Jadid melalui Ekoproteksi - Fathony, Alvan; Rokaiyah, Rokaiyah; Mukarromah, Sofiyatul (Universitas Nurul Jadid, 2021)
Islamic Boarding School is one of the institutions that has a lot of potential, including economic potential. To increase this potential is a challenge for pesantren in order to prosper the economy of the pesantren itself and the wider community. The economic independence of Nurul Jadid Islamic boarding school cannot be seen from the building which is currently developing rapidly. The spirit of independence of the santri that is formed can be a potential for the pesantren to improve the economic stability of the pesantren. One of the efforts to make Nurul Jadid Islamic boarding school independent is through a business unit. Where a well-organized business will provide output with good income. In economic management, Islamic boarding schools need an instrument as a guarantee for smoothness and convenience, as well as business protection that has been actively played by the pesantren community. The instrument that is considered appropriate is ecoprotection. Ecoprotection is protection in order to make Islamic boarding schools independent and create or break away from dependence and build and maintain its existence, through an economy that is actualized in the function of economic management, economic independence is needed so that Islamic boarding schools can develop and be sustainable as part of their contribution to the nation's moral education. There are 3 pillars of economic business unit development, including creating a climate that allows the potential of the pesantren community to develop, strengthening the potential of the pesantren community and protecting its economic business units. The management process of the economic business unit at the Islamic boarding school and its development has a very positive impact on achieving mutual prosperity. The positive impact can be seen in several ways; a) the creation of a pattern of community cadres (santri and society) that are independent in the economic field, b) the formation of independent Islamic boarding schools in the economic sector, c) making pesantren as partners for the government, and d) being able to raise the economy of the people (the economy of the community around the pesantren and society as well)